Grammatical Error Made by EFL Learners of STIBA Persada Bunda in Thesis Proposal - Maspufah (Lectura : Jurnal Pendidikan, 2019)
Writing is regarded as one of difficult skill in learning English because it needs more effort to elaborate a complex process of generating, organizing, and revising ideas on a paper. Since English is not students’ mother tongue, error might be occurred in their writing. This research was intended to identify the types and the causes of error made by EFL learners of STIBA Persada Bunda in thesis proposal. It was a descriptive research. Thirteen students from the eighth semester of 2018-2019 academic years were taken for the sample. The instruments used to collect the data were in quantitative and qualitative form. Students’ thesis proposals were taken for quantitative data. Interview was used for qualitative data. The result showed that there were four types of grammatical error found in EFL learners’ thesis proposal: addition, omission, misformation, and misordering. The Errors in their thesis proposal were caused by three conditions: inter-lingual, intra-lingual, and communication strategy-based error. Inter-lingual occurred because of first language interfere when transferring from first language to target lnguage. Intra-lingual occurred in the incomplete rule application and exploiting redundancy. Avoidance caused communication strategy-based error. It could be concluded that EFL learners’ competence in writing needed to be improved as there were many grammatical errors occurred in their thesis proposal.